Regeneration of human body parts via tissue engineering and regenerative medicine: a brief insight into the technology from Islamic perspective - Mohamad, Mohd Yusof; Sha'ban, Munirah (Revelation and Science, IIUM, 2015)
Tissue engineering and regenerative medicine (or, T.E.R.M.) field has been progressing well during the last few decades. Most of T.E.R.M. related studies indicated promising research findings in tissue reconstruction and regeneration. Successful tissue reconstruction and regeneration requires a great balancing acts of the three T.E.R.M. elements or principles namely (1) quality cells source, (2) appropriate biomaterial scaffolds and (3) adequate signalling factors i.e. physical and/or chemical stimuli. From its theoretical framework, this multidisciplinary biomedical technology will enable us to restore, delay or even reverse the aetiology of diseases. It is anticipated that T.E.R.M. will augment current practices in tissue or organ transplantations. It would serve as a potential solution for the lack of tissues or organs donor. Taking advantage of a fully autologous system or approach, T.E.R.M. will help minimize the risk of infection and the issues of rejection (or, adverse host reaction). It is expected that millions of people would be benefited from T.E.R.M. in the near future. This initiative is worth to explore and must be given due consideration by Muslims since there are growing demands for a shari’ah compliance biomedical application. Despite much hopes and expectations, T.E.R.M. has been confronted with some questions arising from the social, cultural and/or religious implications of this new-found knowledge and technology. Based on the available literatures, most of the countries around the world support this highly technical T.E.R.M. research for it is rapidly advancing the understanding of the human tissue regeneration. Although T.E.R.M. is potentially beneficial to improve the health of people, this newly found technology can also be misused. In some cases, it is difficult to differentiate whether T.E.R.M. falls under a pure scientific research or a medical technology innovation that can be applied directly onto patient. The choice in relation to scientific or legal aspects could raise ethical dilemmas as well as religious issues. It affects various stakeholders i.e. patients, medical professionals, and public at large. In order to address the complexity, this present paper intends to explore the principles of T.E.R.M. in terms of tissue regeneration aspects in modern science and Islam, based on the two sources of knowledge i.e. the Qur’an and Hadith (sayings and actions of the Prophet S.A.W.). Emphasis is given on the usage of foreign materials as well as the issues of seeking best treatment and utilizing unlawful things. Refraining from giving an ultimate Islamic decree, the approach is taken to nudge or instigate a discussion on certain issues pertaining to research and application of T.E.R.M. which is still under-represented. Initiation on the foundation of the subject should be ventured further. It is also hoped that the content of this paper will be well received by the readers, and the brief discussion will be enlightening and educational for those who are interested in this important subject.